A combination of an organic alloy and a heterojunction towards a rod–tail helix architecture with dual-color-emitting properties. Issue 31 (4th August 2020) - Zhang, Hongyang; Wang, Haitao; Qian, Peng-Cheng; Wong, Wai-Yeung
Abstract : An unprecedented core–shell structure was constructed by a co-assembly process. The organic alloy BA0.72 BN0.28 can deposit on the BA rod via a solution-epitaxy first and then spread out at the tip by turning it into its original helical morphology. Abstract : An organic alloy can be regarded as a homogeneous solid solution wherein an isostructural molecule is randomly distributed in a host molecule, compared to an organic heterojunction where dissimilar materials generate an interface between two layers or regions. Herein, we fabricate an unprecedented novel BA@BA0.72 BN0.28 heterostructure with a rod–tail helix configuration, in which the helical dual-component BA0.72 BN0.28 alloy can be grown in a controllable manner onto the mono-component BA microrod, forming an organic core–shell micro-structure. In particular, the process of co-assembly formed could be described as the combined construction of an organic alloy and a heterojunction, and the co-assembly possesses the distinctive property of dual-color luminescence. This complex heterostructured architecture is achieved through a stepwise seed-induced growth method and the present solution-phase route allows us to construct more sophisticated organic luminescent heterostructured materials.